PERANCANGAN SISTEM PENJUALAN DAN PREDIKSI PERSEDIAAN STOK BARANG MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING BERBASIS WEB PADA TOKO DY COMPUTER - Deza Farras Tsany; Bagus Mulyawan; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Lack of media promotion at DY Computer and difficulty in detemining the stock of goods in the next period, then designed the system of sale an stock estimates of goods using double exponential smoothing based on web in DY Computer. Through web application is expected to be media promotion, to minimize human error, and to make it easier for determining the stock of goods in the next period. Input data used to prediction is product sales data and output data in the form of prediction in the next period. Data predictions is used should not less than 3 (three) month, to maintain the consistent data in prediction stock of goods. The evaluation result of this design is shown in the value of Mean Absolute Error (MAE) and Mean Square Error (MSE). The Minimum MAE 0,7964 and the highest MAE 27,771.